Corporate Governance, Disclosure Content and Shareholder Value - Jizi, Mohammad (2013)
The recent financial crisis was the largest shock to the financial system in decades. Its implications on banks' performance, corporate image and stakeholders' trust are of a high concern for all interested parties. Banks market capitalisation dropped significantly, risk levels increased and stakeholders’ confidence was shaken. This raises the importance of researching this particular area of primary concern to seek potential approaches intended to help banks to recover through increased disclosures, helping to rebuild trust and manage risk levels. Acknowledging societal needs and having effective dialogue with shareholders and stakeholders regarding banks' social profile as well as risk management practices is likely to reduce the uncertainty gap, shape banks' image and manage trust. These are indeed valuable in the wake of the financial crisis for bank continuity and enhancing shareholder value. I argue that effective corporate governance is likely to encourage more corporate social responsibility (CSR) and risk management (RM) disclosure, which in turn is expected to improve stock prices and reduce return volatility. The study examines potential solutions that assist in the management of the increasing risk levels, shaken confidence and falling market values resulting from the recent financial crisis. It contributes toward better understanding to the influence of internal corporate governance mechanisms on CSR and RM disclosure content and their substantive consequences on shareholder value. Examining a sample of US national commercial banks in the wake of the financial crisis indicates that boards with larger size, higher independence and CEO duality are inclined toward reporting a wider range of CSR and RM disclosures in annual reports, aiming to benefit the bank’s transparency and stakeholders’ long-term mutual relationship. Contrary to CSR disclosures, the number of audit committee financial experts was found to encourage better RM disclosure content implying the difference in influence on voluntary and mandatory disclosures. Insights into the desirable consequences CSR and RM disclosures content have on shareholder value are also evidenced. The study finds evidence supporting the association between CSR disclosure content and stock return indicating investors’ interest in, and consideration of, CSR information when valuing assets and building their trading decisions. The results also suggest that higher RM disclosure score reduces uncertainties of bank risk environment and provides investors with valuable information to assess financial assets and monitor management practices. This was reflected as an improvement to stock return and reduction to return volatility. Thus, effective corporate governance is more tending to enhance shareholder value through encouraging better CSR and RM disclosure content. Corporate governance should sponsor and introduce the perception of doing business responsibly and benefit from RM disclosure as a preventive tool assisting in the management of agency problems and bank risks. The economic consequences of CSR and RM disclosures imply that CSR engagement and reporting is an investment rather than an expense, and RM disclosure is a preventive tool rather than an exercise to comply with legislation requirement. Consequently, considering their content is important for better shareholder value.